Ergonomics characteristics of computer users based on the transtheoretical model-stage of change - HR Alipour Abdoli; H Sanai Nasab; F valipour; M Sepandi (فصلنامه ابن سینا, 2016)
Background: Pay no attention to ergonomics principles among computer users may lead to physical health problems and loss of productivity. The aim of this study was to determine the ergonomics characteristics among computer users in the Baqiyatallah Hospital based on transtheoretical model-stage of change.